An Analysis of Students' Understanding of Multiplication and Division Concepts Using HOTS Questions in Terms of APOS Theory - Siti Faizah; Wan Marzuki Wan Jaafar; Sri Rahayuningsih; Slamet Arifin; Siti Mas’ula; Kaisra Alfikri Islami; Sijah Mariani; Sudirman Sudirman (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
Understanding concepts in mathematics is a very important ability. Because almost all activities in everyday life are related to mathematics. This study aims to explore fourth grade elementary students' understanding of the concepts of multiplication and division using HOTS questions in terms of APOS theory. This type of research is qualitative using an explorative descriptive approach. The research subjects were 6 students who had been selected based on the criteria of high, medium and low scores. Data collection techniques in the study used interviews, tests and documentation. From the results of the study it was found that students' understanding of concepts related to multiplication and division using HOTS questions in terms of APOS theory experienced significant differences. Students with high concept understanding criteria are able to reach the schema stage. Students with moderate concept understanding, still find it difficult at the process stage to the scheme. This is because these students have not been able to identify the type of problem included in the multiplication or division problem. Meanwhile, students in the low category have not been able to reach the action stage. Students who fall into this low category find it difficult when distinguishing which ones include multiplication problems and which ones include division problems, so that at the action stage they are unable to write what is known, asked until the answer. This is a serious concern for all of us to continue to pay attention to the continuity of learning, especially mathematics on multiplication and division material. For educators, this study highlights the importance of explicitly teaching problem structures, operation identification, and meaning-making in context. For curriculum developers, integrating APOS-informed tasks into learning materials and assessments could enhance conceptual understanding from early grade.